Unlawful Acts of Transferring Inherited Objects to Other Parties Without the Knowledge of All Heirs (Study of Decision 75/PDT.G/2017/PN Praya) - Fadhila Rizqi; Fully Handayani Ridwan (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Civil agreements between individuals are not free from unlawful acts. Violations often occur due to agreements made by unauthorized persons, especially in terms of buying, selling, and transferring rights to an object of the agreement. As in the case of Decision 75/PDT.G/2017/PN Praya, violations were found due to the transfer of rights to inherited land without the knowledge of all authorized heirs. This dispute occurs simultaneously in two legal actions, the first legal act, the right to the inherited land is transferred by one of the heirs of the owner to someone who is not authorized to the land, which then by the unauthorized person, the inherited land that does not belong to him is sold to the third party, another as the subject of the land purchaser. This study is aimed at elaborating why the agreement that arose the case was categorized as PMH. The research method used is normative juridical, accompanied by primary and secondary legal materials. The problem approach used is the statutory approach, where the regulation that becomes the main reference is the Civil Code. The results of the study state that violations arise as a result of the actions of the perpetrators contradicting the rights of others, with their obligations, and the moral norms. These violations are categorized as PMH, because there is an act by the perpetrator that triggers a loss to another party, meaning that there is a causal correlation between the act and the loss